F=72
g=6
------------
![\cos { \left( F \right) } =\frac { { e }^{ 2 }+{ g }^{ 2 }-{ f }^{ 2 } }{ 2eg }](https://tex.z-dn.net/?f=%5Ccos%20%7B%20%5Cleft%28%20F%20%5Cright%29%20%20%7D%20%3D%5Cfrac%20%7B%20%7B%20e%20%7D%5E%7B%202%20%7D%2B%7B%20g%20%7D%5E%7B%202%20%7D-%7B%20f%20%7D%5E%7B%202%20%7D%20%7D%7B%202eg%20%7D%20)
Therefore:
![\cos { \left( 72 \right) } =\frac { { e }^{ 2 }+{ 6 }^{ 2 }-{ f }^{ 2 } }{ 2\cdot e\cdot 6 } \\ \\ \cos { \left( 72 \right) } =\frac { { e }^{ 2 }+36-{ f }^{ 2 } }{ 12e }](https://tex.z-dn.net/?f=%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%3D%5Cfrac%20%7B%20%7B%20e%20%7D%5E%7B%202%20%7D%2B%7B%206%20%7D%5E%7B%202%20%7D-%7B%20f%20%7D%5E%7B%202%20%7D%20%7D%7B%202%5Ccdot%20e%5Ccdot%206%20%7D%20%5C%5C%20%5C%5C%20%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%3D%5Cfrac%20%7B%20%7B%20e%20%7D%5E%7B%202%20%7D%2B36-%7B%20f%20%7D%5E%7B%202%20%7D%20%7D%7B%2012e%20%7D)
![\\ \\ 12e\cdot \cos { \left( 72 \right) } ={ e }^{ 2 }+36-{ f }^{ 2 }\\ \\ \therefore \quad { f }^{ 2 }={ e }^{ 2 }-12e\cdot \cos { \left( 72 \right) } +36\\ \\ \therefore \quad f=\sqrt { { e }^{ 2 }-12e\cdot \cos { \left( 72 \right) +36 } } \\ \\ \therefore \quad f=\sqrt { e\left( e-12\cos { \left( 72 \right) } \right) +36 }](https://tex.z-dn.net/?f=%5C%5C%20%5C%5C%2012e%5Ccdot%20%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%3D%7B%20e%20%7D%5E%7B%202%20%7D%2B36-%7B%20f%20%7D%5E%7B%202%20%7D%5C%5C%20%5C%5C%20%5Ctherefore%20%5Cquad%20%7B%20f%20%7D%5E%7B%202%20%7D%3D%7B%20e%20%7D%5E%7B%202%20%7D-12e%5Ccdot%20%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%2B36%5C%5C%20%5C%5C%20%5Ctherefore%20%5Cquad%20f%3D%5Csqrt%20%7B%20%7B%20e%20%7D%5E%7B%202%20%7D-12e%5Ccdot%20%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%2B36%20%7D%20%20%7D%20%5C%5C%20%5C%5C%20%5Ctherefore%20%5Cquad%20f%3D%5Csqrt%20%7B%20e%5Cleft%28%20e-12%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%20%5Cright%29%20%2B36%20%7D%20)
But what is e?
E=76
G=32
g=6
And:
![\frac { e }{ \sin { \left( E \right) } } =\frac { g }{ \sin { \left( G \right) } }](https://tex.z-dn.net/?f=%5Cfrac%20%7B%20e%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%20E%20%5Cright%29%20%20%7D%20%20%7D%20%3D%5Cfrac%20%7B%20g%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%20G%20%5Cright%29%20%20%7D%20%20%7D%20)
Which means that:
![\frac { e }{ \sin { \left( 76 \right) } } =\frac { 6 }{ \sin { \left( 32 \right) } } \\ \\ \therefore \quad e=\frac { 6\cdot \sin { \left( 76 \right) } }{ \sin { \left( 32 \right) } }](https://tex.z-dn.net/?f=%5Cfrac%20%7B%20e%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%2076%20%5Cright%29%20%20%7D%20%20%7D%20%3D%5Cfrac%20%7B%206%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%2032%20%5Cright%29%20%20%7D%20%20%7D%20%5C%5C%20%5C%5C%20%5Ctherefore%20%5Cquad%20e%3D%5Cfrac%20%7B%206%5Ccdot%20%5Csin%20%7B%20%5Cleft%28%2076%20%5Cright%29%20%20%7D%20%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%2032%20%5Cright%29%20%20%7D%20%20%7D%20)
If you take this value into account, you will discover that f is...
![f=\sqrt { \frac { 6\cdot \sin { \left( 76 \right) } }{ \sin { \left( 32 \right) } } \left( \frac { 6\cdot \sin { \left( 76 \right) } }{ \sin { \left( 32 \right) } } -12\cos { \left( 72 \right) } \right) +36 } \\ \\ \therefore \quad f=10.8\quad \left( 1\quad d.p \right)](https://tex.z-dn.net/?f=f%3D%5Csqrt%20%7B%20%5Cfrac%20%7B%206%5Ccdot%20%5Csin%20%7B%20%5Cleft%28%2076%20%5Cright%29%20%20%7D%20%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%2032%20%5Cright%29%20%20%7D%20%20%7D%20%5Cleft%28%20%5Cfrac%20%7B%206%5Ccdot%20%5Csin%20%7B%20%5Cleft%28%2076%20%5Cright%29%20%20%7D%20%20%7D%7B%20%5Csin%20%7B%20%5Cleft%28%2032%20%5Cright%29%20%20%7D%20%20%7D%20-12%5Ccos%20%7B%20%5Cleft%28%2072%20%5Cright%29%20%20%7D%20%20%5Cright%29%20%2B36%20%7D%20%5C%5C%20%5C%5C%20%5Ctherefore%20%5Cquad%20f%3D10.8%5Cquad%20%5Cleft%28%201%5Cquad%20d.p%20%5Cright%29%20)
So I would have to say that the answer is approximately (c).
Answer:
C
Step-by-step explanation:
1 | 4 6 - 2
4 10
------------------
4 10 8 ← remainder
Answer: The solution is the ordered pair (1/2, -3/4) so x = 1/2 and y = -3/4 pair up together. The two lines, when graphed, cross at this location.
note: 1/2 = 0.5 and -3/4 = -0.75; so the intersection point can be written as (0.5, -0.75)
===================================================
Explanation:
The second equation has y isolated. We can replace the y in the first equation with the expression 1/2x - 1
3x + 2y = 0
3x + 2( y ) = 0
3x + 2( 1/2x - 1) = 0 ... y is replaced with 1/2x-1
3x + 2(1/2x) + 2(-1) = 0 .... distribute
3x + x - 2 = 0 .... note how 2 times 1/2 is 1
4x - 2 = 0
4x = 2
x = 2/4
x = 1/2
Use this x value to find the y value it pairs with
y = (1/2)*x - 1
y = (1/2)*(1/2) - 1 ... replace x with 1/2
y = 1/4 - 1
y = 1/4 - 4/4
y = (1-4)/4
y = -3/4
Y > |x| + 5
<span>(0,5) when x = 0, y > 5 ...FALSE
</span>(1,7) when x = 1, y > 6 ...7>6...TRUE
(7,1) when x = 7, y > 12 ...FALSE
answer
<span>B.(1,7)</span>
Answer:
Blue square
Step-by-step explanation:
looking like rhombus because right angle is 90 degrees and a square has 4 right angles